A New Differential Magnetic-Field Probe With Parasitic Elements for Near-Field Scanning - Lei Wang; Xiaoxian Liu; Guoguang Lu; Zhangming Zhu (IEEE Photonics Journal)
Herein, A new differential magnetic-field probe with parasitic elements is presented. The proposed probe has two pairs of shorted differential loops as parasitic elements, which could enhance the detection sensitivity owing to the increased detection area. The proposed probe comprises a U-shaped loop with two outputs as the driven element, two pairs of shorted differential loops as parasitic elements, a pair of shorted via, a pair of connected via, and many shielded vias. First, the usual single-loop probe is theoretically studied. Second, a pair of shorted loops is inserted into the differential single-loop probe as a parasitic element to receive more magnetic flux. Third, another pair of shorted loops is etched into the probe to further improve the detection sensitivity. The corresponding simulation results are presented to prove the effectiveness of the design. Finally, the proposed probe with parasitic elements is designed, printed, and evaluated. Measurement results reveal that the designed probe has high detection sensitivity.